Symbolic Modification and Declining Community Participation in Cultural Traditions: A Study of the Ngarot Ritual in Tugu Village, Indramayu, West Java - Siga, Willfridus Demetrius; Waruwu, Dominikus; Fransiska, Federika; Joshua, Marchelino (FOCUS, 2025)
This study aims to analyze the impact of modification on the declining community participation in the Ngarot ceremony in Tugu Village, Lelea Subdistrict, Indramayu Regency. Ngarot is an agrarian tradition that emphasizes the regeneration of cultural values through the active involvement of youth. Unlike Lelea Village, which has preserved the symbolic structure and educational function of Ngarot, Tugu Village has undergone format changes—such as the removal of agricultural training, the addition of religious recitations (pengajian), and entertainment—that have led to a disorientation of meaning and decreased engagement among younger generations. This study employs a qualitative approach using a descriptive-interpretative method. Data were obtained through interviews, observation, and document analysis, and were analyzed thematically and reflectively. The findings reveal that modifications that disregard the cultural structure of meaning can trigger symbolic alienation, interpretive conflict between cultural and religious narratives, and a sustainability crisis in traditional practices. The original contribution of this research lies in mapping the relationship between local policy, symbolic transformation, and cultural participation. This study recommends a contextual meaning-based preservation model and active youth engagement as an alternative approach to sustaining traditions amid ongoing social change.